Dysbiosis of Gut Microbiota With Reduced Trimethylamine‐N‐Oxide Level in Patients With Large‐Artery Atherosclerotic Stroke or Transient Ischemic Attack. Issue 11 (November 2015) - Yin, Jia; Liao, Shuo‐Xi; He, Yan; Wang, Shan; Xia, Geng‐Hong; Liu, Fei‐Tong; Zhu, Jia‐Jia; You, Chao; Chen, Qiong; Zhou, Liang; Pan, Su‐Yue; Zhou, Hong‐Wei
Abstract : Background: Gut microbiota has been suggested to play a role in almost all major diseases including cardio‐ and cerebrovascular diseases. A possible mechanism is the transformation of dietary choline andl ‐carnitine into trimethylamine by gut bacteria. This metabolite is further oxidized into trimethylamine‐N‐oxide (TMAO) in liver and promotes atherogenesis. Nevertheless, little is known about gut microbial diversity and blood TMAO levels in stroke patients. Methods and Results: We performed a case‐control study of patients with large‐artery atherosclerotic ischemic stroke and transient ischemic attack. TMAO was determined with liquid chromatography tandem mass spectrometry. Gut microbiome was profiled using Illumina sequencing of the 16S rRNA V4 tag. Within the asymptomatic control group, participants with and without carotid atherosclerotic plaques showed similar levels of TMAO without a significant difference in gut microbiota; however, the gut microbiome of stroke and transient ischemic attack patients was clearly different from that of the asymptomatic group. Stroke and transient ischemic attack patients had more opportunistic pathogens, such as Enterobacter, Megasphaera, Oscillibacter, and Desulfovibrio, and fewer commensal or beneficial genera including Bacteroides, Prevotella, and Faecalibacterium . This dysbiosis was correlated with the severity of the disease. The TMAO level in the stroke and transient ischemic attack patients was significantly lower, rather than higher, than that of the asymptomatic group. Conclusions: Participants with asymptomatic atherosclerosis did not exhibit an obvious change in gut microbiota and blood TMAO levels; however, stroke and transient ischemic attack patients showed significant dysbiosis of the gut microbiota, and their blood TMAO levels were decreased.